The Nexus of Neuroinflammation and Psychopathology in Neuropsychiatric Systemic Lupus Erythematosus (NPSLE): A Meta-Analysis of Anti-NMDAR, Anti-Ribosomal P Antibodies, and Psychosomatic Manifestations (Depression, Anxiety, Cognitive Dysfunction) - Anggi Setiawan; Arina Widya Murni (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Neuropsychiatric systemic lupus erythematosus (NPSLE) significantly impacts patients through diverse neurological and psychiatric symptoms, including prevalent psychosomatic manifestations like depression, anxiety, and cognitive dysfunction. Specific autoantibodies, such as anti-N-methyl-D-aspartate receptor (anti-NMDAR) and anti-ribosomal P protein (anti-RP) antibodies, are implicated in its complex neuroinflammatory pathogenesis. This meta-analysis aimed to quantitatively assess the association between these autoantibodies and these key psychosomatic outcomes in NPSLE. Methods: A systematic literature search of PubMed, EMBASE, Scopus, and PsycINFO (2014-2024) identified observational studies reporting on anti-NMDAR or anti-RP antibodies and depression, anxiety, or cognitive dysfunction in adult NPSLE patients. Data from six eligible studies (850 patients) were extracted and quality was assessed. Pooled odds ratios (ORs) or standardized mean differences (SMDs) were calculated using a random-effects model, with heterogeneity and publication bias evaluated. Results: Anti-NMDAR antibody positivity was significantly associated with increased odds of cognitive dysfunction (OR = 2.85, 95% CI = 1.90-4.28). Anti-RP antibody positivity was significantly linked to increased odds of depression (OR = 3.20, 95% CI = 2.15-4.76) and anxiety (OR = 2.50, 95% CI = 1.65-3.78). Moderate heterogeneity was noted for some analyses. Conclusion: This meta-analysis highlights distinct associations: anti-NMDAR antibodies with cognitive dysfunction, and anti-RP antibodies with depression and anxiety in NPSLE. These findings underscore the potential role of these autoantibodies in specific psychosomatic symptom clusters, guiding further research and clinical consideration in NPSLE management.